2014
DOI: 10.14294/water.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This article reviews recent reports on large water clusters containing millions to billions of water molecules directly imaged under the transmission electron microscope and atomic force microscope, which are created by repeated dilution of aqueous solutions of polar solutes and also apparently by other means, and offers an explanation of the structures based on special spherical dipoles originating from quantum coherent domains predicted from quantum electrodynamics theory. IntroductionStable water clusters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This model explains the physical existence and properties of magnetized water and homeopathic medicines. As coherent domains of Del Giudice and Preparata can be identified with EZ water, 104 the Nanoparticle-Exclusion Zone Shell Model covers coherent domains model and also clathrate model at least in spirit that "memory" is the cause of the effect.…”
Section: Discussionmentioning
confidence: 99%
“…This model explains the physical existence and properties of magnetized water and homeopathic medicines. As coherent domains of Del Giudice and Preparata can be identified with EZ water, 104 the Nanoparticle-Exclusion Zone Shell Model covers coherent domains model and also clathrate model at least in spirit that "memory" is the cause of the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Especially interesting is that these supramolecular water complexes (clusters, associates) are present in high and ultra-high dilutions of different substances obtained by repeated dilutions of polar solutes. They may be visualized using such physical methods as atomic force microscopy, transmission electron microscopy, electric force microscopy, nanoparticle tracking analysis, dynamic light scattering (for the reviews see [33][34][35][36][37]). Many authors who observed the appearance of supramolecule water complexes in aqueous systems suppose that they represent the so-called coherent domains (CDs) of water predicted by Emilio Del Giudice and colleagues [38].…”
Section: Discussionmentioning
confidence: 99%
“…The coherent domains model of Del Giudice et al is well rooted in quantum field theory, but lacks direct experimental support (Bellavite et al, 1, 2013). It suggests that interaction between the ambient electromagnetic field and liquid water induces the formation of stable coherent domains of about 100 nm in diameter, "responsible for all the special properties of water including life itself" (Ho, 2014), as observed by Konovalov et al (2014a,b). Del Giudice et al (2010) also suggest that exclusion zone (EZ) water is a macroscopic coherent domain.…”
Section: Introductionmentioning
confidence: 75%